Moderated online social therapy for carers of young people recovering from first-episode psychosis: study protocol for a randomised controlled trial. Issue 1 (December 2017) - Gleeson, John; Lederman, Reeva; Herrman, Helen; Koval, Peter; Eleftheriadis, Dina; Bendall, Sarah; Cotton, Sue; Alvarez-Jimenez, Mario
Abstract Background First-episode psychosis most often has its onset during late adolescence. In caring for the young person, families endure high levels of stress and depression. Meanwhile, the social networks of families often erode. Our group has previously shown that family cognitive behaviour therapy (CBT) leads to significantly improved perceived stress compared with specialist first-episode treatment as usual; however, there are well-known barriers to the dissemination of effective family interventions. To address this, we have developed a novel online intervention entitled 'Altitudes' that fully integrates purpose-built online social networking, expert and peer moderation, and evidence-based psychoeducation within a single application. The primary aim of this trial is to evaluate the effectiveness of Altitudes in reducing stress in carers over a 6-month period. Methods/design We describe here a single-blinded cluster randomised controlled trial (cRCT) with permutated blocks. The clusters comprise individual families. The two treatment conditions include Altitudes plus Specialist Treatment as Usual (STAU) and STAU alone. Altitudes involves participation in our novel online programme whereas STAU comprises specialist family work at the Early Psychosis Prevention and Intervention Centre (EPPIC), Melbourne, Australia. We aim to recruit 160 family members of young, 15–27 year-old, patients registered for treatment for first-episode psychosis (FEP) at EPPIC. The design includes two assessment time points, namely, baseline and 6-month follow-up. The study is due for completion within 2 years including an 18-month recruitment period and a 6-month treatment phase. The primary outcome is carers' perceived stress at 6 months. Secondary outcome measures include a biomarker of stress, depressive symptoms, worry, substance use, loneliness, social support, satisfaction with life, and a range of measures that tap into coping resources. We seek to gain a dynamic picture of carer stress through our Smartphone Ecological Momentary Assessment (SEMA) tool. Discussion This is the first randomised controlled trial designed to evaluate an online intervention for carers of young people recovering from FEP. It has the potential to produce evidence in support of a highly novel, accessible, and cost-effective intervention to reduce stress in carers who are providing support to young people at a critical phase in their recovery from psychosis. Trial registration Australian New Zealand Clinical Trial Registry, identifier:ACTRN12616000968471 . Retrospectively registered on 22 July 2016.